Studying the effect of tillage depth combined with organic amendments and different nitrogen fertilization on improving calcareous soil properties and wheat productivity - Adel S. El-Hassanin; Magdy R. Samak; Mohamed E. El-Fayuomy; Azza R. Ahmed; Nesreen S. Asem (Universitas Sebelas Maret, 2025)
Calcareous soil suffers from deprived organic materials, structural properties, increased water holding capacity, deep percolation, crusts and cracks formation, which hinders the roots dispersion and decreases permeation speed. This inhibits the soil physical, hydraulic properties, and its nutritional status. The research objective is to enhance the calcareous soil status and its productivity using eco-friendly conditioners. A Split-split plot field experimental study has been laid at El-Nubaria Agri. Res. Stat., in 2018 and 2019 winter seasons with three replications. The main factor was two depths of tillage: (T1) surface tillage (0 – 15 cm) and (T2) deep tillage (0 – 60 cm). The sub-main factor was three types of mineral nitrogen (N) fertilization, control (C1) without N application, ammonium nitrate (F1) and urea formaldehyde (F2), while the sub-sub main factor was the types of soil amendments: no amendment (cont.), sugar beet waste (W), K-Humate (KH), Sulphur (S) and compost (Comp). Results have indicated that greater values of organic matter OM and aggregate measured were gained by the surface tillage treatment and using both sugar beet wastes (W) and compost applications. The combination between the deep tillage (T2) and ammonium nitrate (F1) and sugar beet waste (W) has increased the wheat grains and straw yield (ton ha-1) and 1000-grains weight (g). Sugar beet waste can be recommended as an economic conditioner enhances the calcareous soil to make it more productive.